OPTIMIZATION OF PHARMACEUTICAL WASTEWATER TREATMENT BY BIOSORPTION USING GENETIC ALGORITHM - Hasan Abdallah, Ola Belal; Dwivedi, Priy Brat (Green Chemistry & Technology Letters, 2021)
Purpose of the study: Optimizing the process of pharmaceutical wastewater treatment by biosorption using a genetic algorithm. Methodology: The main steps followed were, determination of the wavelength at maximum absorbance (Î»max), drawing the calibration curve between the absorbance and the concentration of diclofenac sodium, designing the experiment using Design-Expert software, finding the percentage removal of diclofenac sodium for each run, obtaining the model equation of the analysis, finding the optimized condition using genetic algorithm in MATLAB software, running the experiment at the optimized conditions and analyzing the results. Main Findings: The technique used in the optimizing process was effective, in which the percentage removal was obtained as 8.73% at the optimized conditions. It was equivalent to 3.43 mg removal / g of activated carbon. Applications of this study: This technique can be applied in different industries especially the chemical and pharmaceutical industries. Novelty/Originality of this study: Using genetic algorithm in order to find the optimized condition of removing diclofenac sodium based on a set of data.